Synthesis and characterisation of photocured biobased polyesters for soft tissue engineering application - Keerthana A/P Rangasamy 1995- author 639620; Farah Hidayah Jamaludin 611706 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Bio-Perubatan)) - Universiti Teknologi Malaysia, 2018